SEXUAL SLAVERY BEFORE AD HOC INTERNATIONAL CRIMINAL TRIBUNALS AND THE INTERNATIONAL CRIMINAL COURT - Szpak, Agnieszka (European Scientific Journal, ESJ, 2013)
The article presents the creation of the International Criminal Tribunal for the former Yugoslavia (ICTY) and the International Criminal Tribunal for Rwanda (ICTR) as well as their jurisdiction. The article continues with the explanation of the terms enslavement and sexual slavery in the way that they were defined in the jurisprudence of the ad hoc international criminal tribunals mostly in the ICTY. The Statutes of both ICTY and ICTR enumerate enslavement as a crime against humanity whereas this is not the case with sexual slavery. This crime is expressly included in the International Criminal Court Statute (ICC) and in the Statute of the Special Court for Sierra Leone (SCSL). Still especially in one case before the ICTY the Tribunal dealt with a crime against humanity of sexual slavery and decided the case – although – not having jurisdiction over a crime so named. This was the case of Kunarać, Kovać and Vuković, which the author analyses in the article. In the end, the author mentions the ICC Statute and the provisions as well as jurisprudence of the SCSL on sexual slavery. Finally the author reaches some interesting conclusions.